2007
DOI: 10.1136/bmj.39280.509803.be
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as an adjunct to exercise based physiotherapy for osteoarthritis of the knee: randomised controlled trial

Abstract: Acupuncture as an adjunct to exercise based physiotherapy for osteoarthritis of the knee: randomised controlled trial Nadine E Foster, senior lecturer in therapies (pain management), 1 Interventions Advice and exercise (n=116), advice and exercise plus true acupuncture (n=117), and advice and exercise plus non-penetrating acupuncture (n=119). Main outcome measures The primary outcome was change in scores on the Western Ontario and McMaster Universities osteoarthritis index pain subscale at six months. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
230
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(234 citation statements)
references
References 31 publications
3
230
1
Order By: Relevance
“…Exercise, including local strengthening exercise and general aerobic exercise, has consistently been shown to be beneficial for older adults with knee pain. Exercise can improve function and reduce pain (2,3), improve physical performance (including walking distance and stair climbing [4]), improve muscle strength, increase joint range of motion and walking speed (5,6), and increase self-efficacy (7). In addition, it has wider health benefits, such as reducing the risk of cardiovascular disease (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise, including local strengthening exercise and general aerobic exercise, has consistently been shown to be beneficial for older adults with knee pain. Exercise can improve function and reduce pain (2,3), improve physical performance (including walking distance and stair climbing [4]), improve muscle strength, increase joint range of motion and walking speed (5,6), and increase self-efficacy (7). In addition, it has wider health benefits, such as reducing the risk of cardiovascular disease (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term improvements in health outcomes, reduced use of antiinflammatory drugs, and high patient satisfaction were achieved by giving patients with knee osteoarthritis greater access to community physiotherapy (individualised exercise programme; advice on activity and pacing) and pharmacists (face-to-face medication review and advice). In separate trials we have confirmed the benefits of advice and exercise for knee osteoarthritis, that acupuncture yields no additional benefit, 13 and that for hand osteoarthritis joint protection education offered by occupational therapists is beneficial. …”
Section: Evaluation and Implementation Of New Interventionsmentioning
confidence: 59%
“…Our previous trial results suggested that a lower limb exercise programme that was supervised and progressed over six treatment sessions resulted in greater improvements in pain than one that was provided over an average of four sessions. 34,203 Therefore, the protocol for ITE was developed to ensure the prescription of an individualised, supervised and progressed lower limb exercise programme.…”
Section: Intervention 2: Individually Tailored Exercisementioning
confidence: 99%
“…The Acupuncture, Physiotherapy and Exercise (APEX) trial, 202 which incorporated a more intensive exercise intervention that was supervised and progressed over six treatment sessions, resulted in greater improvements in pain than the exercise programme in the TOPIK trial. 34,203 Similarly, other recent trials 30,98 and reviews 204 showed small to moderate, short-term reductions in knee pain and disability that are not sustained in the long term. 192 Exercise is clearly worth doing but we need to find out if, and how, the beneficial effects can be maintained over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation